Gender-based interpersonal communication in badminton coaching: A qualitative study of male coaches and female athletes - Teguh Dwi Putranto; Made Dinda Windiasari (Sriwijaya Journal of Sport, 2026)
Research Background: Interpersonal communication between coaches and athletes is important in supporting athlete development, motivation, discipline, and performance. In badminton training, effective communication can create a positive training environment and strengthen the relationship between coaches and athletes. Gender differences may also influence communication patterns, so coaches need to apply appropriate communication approaches. However, studies on interpersonal communication between male coaches and female athletes in badminton academies remain limited. Research Objectives: This study aims to determine how female athletes and male coaches at Irwan Badminton Academy foster interpersonal communication. Method: This research uses a qualitative, descriptive approach. The data gathering technique includes interviews, observations, and documentation. The participants in this research totalled 6, comprising 3 male coaches and 3 female athletes at the Irwan Badminton Academy Executive Board. Data analysis used in this study includes data reduction, data presentation, and data interpretation. Results: Positive interactions between coaches and athletes may help athletes develop their social skills and character. Open communication, empathy, and peer support are all skills that athletes will acquire that are useful outside of the athletic arena. This develops athletes into resilient, competitive people in addition to skilled players. Conclusion: Research at Irwan Badminton Academy shows that coaches' communication methods need to be tailored to the athlete's gender. Women athletes tend to require clear and direct instructions, delivered in a supportive manner. They are also more open to feedback, able to accept responsibility, and require a balance between discipline and emotional support. These findings imply that adaptive communication can help coaches optimally develop athletes' potential, create a positive training environment, and improve athletes' motivation and performance in competitions.